Interface Text Writing Strategies in Professional Russian and English Articles - Kseniia P. Krapivina (Виртуальная коммуникация и социальные сети)
Software with graphical interface is a common but linguistically understudied phenomenon. The article describes communicative interface textual content as a message from a composite addressee (customer, developer, interface writer) to the target user. The author applied the methods of comparative and praxeological analysis to identify and classify the strategies used by English- and Russian-language UX interface text authors in professional blogs, which served as metatextual sources of research material. A comparative analysis of strategies employed by different authors made it possible to determine the common and individual strategies, as well as their correlation with linguistic or sociocultural external factors. To achieve such macro-goals as product and brand success, the interface text should inform, instruct, teach (navigation), hold attention, engage, and establish an emotional connection with the user. The research revealed the semantic strategy of clarity/precision, as well as the pragmatic strategy of brevity. They take into account the experience and expectations of the target audience. The English-language authors appealed to various inclusive strategies while the Russian-language authors concentrated on coherence and informativeness. The strategies were implemented using both verbal and paralinguistic methods.